AN ECO-FRIENDLY APPROACHES FOR INSECT PEST MANAGEMENT AND ENVIRONMENTAL - N. USHA, INDHUMATHI RAJAGOPAL KANNAN, K. GAYATHRI, P. SARANRAJ, IADALIN RYNTATHIANG, MUKESH KUMAR DHARMALINGAM JOTHINATHAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
For decades, the control of insect pests has been cost millions to billions in agriculture, with synthetic insecticides being considered the most effective method for pest control. However, their overuse has caused harm to human health, the environment, and beneficial insects, while also fostering pesticide resistance in pests. Developing insect-resistant cultivars through conventional host plant resistance (HPR) is challenging, as it involves complex traits across multiple loci. Despite these difficulties, HPR remains essential for integrated pest management. Significant progress has been made in creating resistant cultivars for various crops, with gene transfer to suitable cultivars for different agro-ecosystems being crucial. Incorporating proteins from wild crop relatives and novel genes, such as those from Bacillus bacteria, can improve HPR. This approach can reduce pest damage, promote beneficial microbes, minimize pesticide use, and delay the development of insecticide resistance.